2020
DOI: 10.1371/journal.pone.0229213
|View full text |Cite
|
Sign up to set email alerts
|

Detection of retinal microvascular changes in von Hippel-Lindau disease using optical coherence tomography angiography

Abstract: Von Hippel-Lindau (VHL) disease is a hereditary disorder that can lead to ophthalmic manifestations, including retinal capillary hemangioma (RCH). The diagnosis of RCH is often guided by wide-field fluorescein angiography. In some cases, optical coherence tomography angiography (OCT-A) serves as a non-invasive alternative to FA. Herein, we used OCT-A to examine the macular microvasculature in patients with VHL disease. Subjects Subjects were selected from patients with a diagnosis of VHL. The control group inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
6
1
Order By: Relevance
“…We used OCTA to investigate macular perfusion in a large VHL population, detecting a reduction in macular blood flow. Our findings differ from those recently found, where an increase in macular vessel density in VHL patients was detected in both SCP and DCP [ 24 ]. However, our results cannot be easily compared when different OCTA commercial software is used and the ICP is partially incorporated into the other plexuses.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We used OCTA to investigate macular perfusion in a large VHL population, detecting a reduction in macular blood flow. Our findings differ from those recently found, where an increase in macular vessel density in VHL patients was detected in both SCP and DCP [ 24 ]. However, our results cannot be easily compared when different OCTA commercial software is used and the ICP is partially incorporated into the other plexuses.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, the presence of tiny clinically undetectable RHs, visible just with fluorescein angiography, cannot be excluded. Another limitation is that genotype-phenotypes correlation was not performed [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Therefore, we cannot exclude that the genotype of VHL germline mutation may differently influence retinal vascular development and perfusion.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Moreover, a pan-retinal effect has been hypothesized in patients with VHL disease even in the absence of RCH. In a recent study by Lu et al, 20 a significant increase in vessel density was found in the macula of patients with VHL disease for both superficial capillary plexus and deep capillary plexus on OCT-A, consistent with the pathogenesis of tumor development in VHL. Furthermore, peripheral non-perfusion, capillary telangiectasia and capillary leakage have been reported using ultra-wide field FA, indicating stimulation of the vascular bed toward angiogenesis in the presence of hypoxia with consequent VEGF production.…”
Section: Discussionsupporting
confidence: 61%
“…In VHL patients, OCT and OCTA have been mainly used to study posterior pole RH or macular capillary changes related to RH [29][30][31][32] . To the best of our knowledge, this is the first OCT and OCTA study investigating the structural and perfusion characteristics of the peripapillary nerve fiber layer, in which glial cells, neurons and capillaries of the radial peripapillary capillary plexus interact.…”
Section: Discussionmentioning
confidence: 99%